Improvement of humoral immunity by repeated dose-intensified COVID-19 vaccinations in primary non- to low-responders and B cell deficient rheumatic disease patients. Issue 135 (February 2023) - ten Hagen, Alexander; Hermann, Sandra; Habermann, Elisa; Frommert, Leonie Maria; Arumahandi de Silva, Amanthi Nadira; Scholz, Veronika; Ghannam, Khetam; Klotsche, Jens; Zernicke, Jan; Alexander, Tobias; Burmester, Gerd-R.; Albach, Fredrik N.; et al.
Abstract: Objective: To determine whether repeated, dose-intensified mRNA vaccinations against COVID-19 increase humoral immunity in previously low-responding patients with autoimmune rheumatic diseases (AIRD), including rituximab-treated and B cell depleted patients. Methods: Of 308 AIRD patients receiving basic immunization, 98 had a low serological response against SARS-CoV-2 with a neutralizing capacity of < 70% using surrogate neutralization assay. 38 patients received a third vaccination with 30 μg BNT162b2 16 weeks after second vaccination. If neutralizing serum capacity was below 70% four weeks after the last vaccination, then the fourth vaccination (n = 19) and the fifth (n = 4) vaccination with 100 μg mRNA-1273 took place eight weeks after the last vaccination. Results: Each of the three booster vaccinations resulted in a significant increase of mean serum neutralizing capacity (3rd: Δ = 42%, p < 0.001; 4th: Δ = 19%, p = 0.049 and 5th: Δ = 51%, p = 0.043) and produced a significant proportion of high-responders (3rd: 34%; 4th: 32% and 5th: 75%). Low B cell counts (p = 0.047), lower previous antibody response (p < 0.001) and rituximab therapy (p = 0.021) were negatively associated with successful response to the third but not to the fourth vaccination. Remarkably, substantial increases in neutralization capacity of up to 99% were observed after repeated vaccinations in B cell depleted patients. Conclusion: AIRD patients with low humoral response benefited from up to three repeated dose-intensified mRNA booster vaccinations – despite low B cell count and previous rituximab therapy. Each additional vaccination substantially reduced the number of low-responding, vulnerable patients. Highlights: Vaccine response to SARS-CoV2 and prognosis may be poor in rheumatic patients. Patients with reduced response received up to three dose-intensified mRNA boosters. Each vaccination significantly improved mean neutralization against SARS-CoV2. Rituximab, low B cells, and low baseline titers were associated with reduced response. Excellent vaccination responses could be induced even without blood B cells.